IMPLEMENTATION OF THE MARKETING MIX FOR EDUCATIONAL SERVICES AT SENIOR HIGH SCHOOL MUHAMMADIYAH 1 YOGYAKARTA - Ridlo, Wildani; Arsila, Yusra; Haeqal, Muhammad; Arifin, Zainal (Prodi Pendidikan Agama Islam STAI Darul Falah, 2025)
This research aims to explore the implementation of marketing strategies for educational services at SMA Muhammadiyah 1 Yogyakarta to attract the interest of prospective new students and maintain the loyalty of existing students by optimizing the marketing mix 7P strategy. This research employed descriptive analytical qualitative research with observation, interviews, and documentation data collection techniques. It revealed that the comprehensive, innovative, and effective marketing mix (7P) was implemented at Muhammadiyah Senior High School 1 Yogyakarta. The school offered superior products, varied prices with scholarship schemes, strategic location, active multi-channel promotion, quality human resources through selective recruitment and competency development, complete facilities, and SNP standard learning process management. This strategy increased public interest by 25-30% (2019-2023) and maintained student loyalty. This research is limited due to exploring marketing strategies for educational services in one private high school in Yogyakarta. Generalizations of findings should be achieved by considering the unique characteristics of each educational institution. Comparative studies with similar educational institutions can be conducted for further research to identify and explore the impact of effective educational service marketing strategies.